The development of PAT‐HD: A co‐designed tool to promote physical activity in people with Huntington's disease. (13th February 2021) - Jones, Una; Hamana, Katy; O'Hara, Fran; Busse, Monica
Abstract: Background: Huntington's disease (HD) is a genetic condition resulting in movement, behavioural and cognitive impairments. People with HD have low levels of physical activity which may be compounded by insufficient support from health‐care professionals. Objective: To evaluate the initial acceptability of a co‐designed tool used within a HD clinic to promote physical activity. Design: Co‐design of a physical activity tool; acceptability evaluation. Setting and participants: Co‐design included people with HD and health‐care professionals. Acceptability was evaluated in a HD clinic in the UK. Main variables studied: A physical activity tool was co‐designed and used within a HD clinic. Main outcome measure: Acceptability as assessed by semi‐structured interviews with members of the HD clinic. Results: Forty people visited the HD clinic; 19 were given physical activity advice. Themes around who, where and how promotion of physical activity could take place were identified; concepts of benefits and barriers were threads through each theme. Discussion: We describe for the first time the co‐design of a HD specific physical activity tool. Our associated acceptability study emphasizes the importance of individualized planning of physical activities in complex neurodegenerative conditions. Perceived barriers were time and lack of knowledge of local resources. Conclusions: A simple tool can support conversations about physical activity with people with HD and is an aid to individualized goal setting. Exploring the use of PAT‐HD within a community setting and development of support systems for health‐care professionals and support workers who are in regular contact with people with HD is required.